Redefining Graduation Exams and the Role of Academic Ability Tests: A Policy Analysis in Shaping Holistic Assessment and Students' Growth Mindset - Tatik; Dedi Rolis; Amar B.K.; Farhan (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
This study aims to analyze the redefinition of graduation exams and the role of the Academic Ability Test (TKA) within the education system. The research employs a descriptive qualitative approach by examining policies and concepts proposed by Prof. Muti regarding the shift in the graduation exam paradigm. The main findings indicate that graduation exams are no longer the sole determinant of student graduation. Instead, graduation is determined by schools based on various aspects of student development, including character and social engagement. Although the TKA is not mandatory, it serves as an indicator of academic ability for further studies and as a component of the achievement track, alongside report card grades and other accomplishments. The implication of this research is the promotion of a growth mindset approach in education, shifting the focus from short-term achievements to students’ continuous development, while fostering optimism and the motivation to keep improving. This policy also promotes holistic assessment that considers academic intelligence, leadership, and social awareness. The originality of this study lies in its comprehensive analysis of the paradigm shift in graduation exams, emphasizing student-centered development beyond mere academic outcomes.